Application of the local cohesive zone method to numerical simulation of composite structures under impact loading. (June 2017) - Shor, Ofir; Vaziri, Reza
Abstract: A novel technique for efficient modelling of progressive delamination in large-scale laminated composite structures is presented and applied to the simulation of two dynamic events involving axial crushing of tubes and transverse impact loading of plates. During the transient analysis, continuum elements that are prone to delaminate are adaptively split through their thickness into two shell elements with cohesive elements planted between them. The numerical results using this adaptive placement of inter-laminar cohesive zones combined with a continuum modelling approach for capturing the intra-laminar damage modes in the composite are compared to the available experimental data as well as to the results obtained using the conventional application of the cohesive zone method, where the discrete cohesive interfaces/elements are introduced prior to the analysis.